2017
DOI: 10.18494/sam.2017.1441
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition and Characterization of Nanocrystalline Ni–B with Low Boron Content for MEMS Applications

Abstract: We fabricated and characterized three kinds of nanocrystalline (NC) Ni-B electrodeposits with low boron content (i.e., 0.05, 0.12, and 0.19 wt.%) for micro-electromechanical system (MEMS) applications. The fabrication was performed by electrodeposition in a nickel sulfamate solution, adjusting the concentration of the boron source, dimethyleamine borane (DMAB). The electrodeposits exhibited high thermal stability, being able to maintain their grain size at 573 K, whereas pure NC Ni started recrystallizing at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The third relates to the electrodeposit properties, where previous studies suggest that increasing the temperature to 60 0 C increases surface roughness or dendrite formation (Gonçalves et al, 2021;Jeon et al, 2022). Kwon et al (2017) found that increasing temperature reduces the hardness of some deposits and increases the grain size.…”
Section: Introductionmentioning
confidence: 99%
“…The third relates to the electrodeposit properties, where previous studies suggest that increasing the temperature to 60 0 C increases surface roughness or dendrite formation (Gonçalves et al, 2021;Jeon et al, 2022). Kwon et al (2017) found that increasing temperature reduces the hardness of some deposits and increases the grain size.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is also reported that Ni-B alloys have a better performance in the under bump metallization (UBM) packaging process comparing to Ni-P. 11 In addition, Kwon et al have reported Ni-B MEMS-based micro-probe for wafer-level integrated circuit tests with a higher stiffness than conventional Ni-Co probe. 12 Furthermore, heat treatment or thermal annealing is a common process applied in fabrication of electronic components, such as the fabrication of MEMS accelerometer. 13 Mechanical properties of electrodeposits are expected to be affected by the heat treatment process.…”
mentioning
confidence: 99%